GLOBALIZATION 3.0 AND UKRAINIAN MODERNIZATION - Сухонос, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The paper attempts to effect qualitatively new type of modern globalization and modernization on development of Ukraine. All societies face this phenomenon in the process of their development, though an issue of choice between the internal and external processes emerges. The article considers a brief history, possible results and consequences of there processes for Ukraine.